PENGARUH SATISFACTION, INVESTMENT SIZE, QUALITY OF ALTERNATIVES TERHADAP BRAND COMMITMENT PADA PENGGUNA SEPATU RUNNING - TERRYCIUS PAOLO FLAVIAN SUNGKAR; WIBISONO SOEDIONO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to know the influence of satisfaction, investment size, and quality of alternatives toward brand commitment on nike running shoes user at DKI Jakarta. This study is using regression analysis for analyzing the data. This study population is nike running shoes uses, and researcher use a purposive sampling method to determine the sample of this study. This study found that there’s significant influence exists satisfaction, investment size and quality of alternatives to brand commitment on nike running shoes user at DKI Jakarta